Differences between fellows and fellowship program directors in their perception of the impact of the COVID-19 pandemic on gastroenterology training: results from a nationwide survey in Greece - Karampekos, George (Ann Gastroenterol, 2020)
BACKGROUND: Lockdown measures applied during the SARS-CoV-2 outbreak caused a significant disturbance to hospital routine. We assessed trainees’ and fellowship directors’ perceptions regarding the impact of the pandemic on gastroenterology fellowship training. METHODS: A web-based survey was anonymously disseminated to all Greek gastroenterology fellows and fellowship program directors. Participants completed electronically a questionnaire comprised of 5 domains that assessed participants’ perception of: 1) overall impact on training; 2) impact on training in gastroenterology-specific fields (endoscopy, inflammatory bowel disease, hepatology); 3) impact on different aspects of endoscopy training; 4) impact on academic training; and 5) training perspectives for the post-pandemic era. RESULTS: A total of 77/128 fellows (60.1%) and 18/28 fellowship program directors (64.3%) responded. More fellows reported that the COVID-19 pandemic would have an adverse impact on fellowship training compared to their fellowship program directors (81.8% vs. 55.6%, P=0.038). This concern was mainly focused on endoscopy training (83.1% vs. 27.8%, P<0.001), with no difference regarding training in gastroenterology’s other specific fields. The difference was consistent for technical skills (79.2% vs. 38.9%, P=0.001), and for the performance of basic diagnostic (70.1% vs. 22.2%, P<0.001) and emergency (48.1% vs. 11.1%, P=0.004) procedures. Fellows and fellowship program directors identified the unknown timeframe of measure implementation and the postponement of scheduled endoscopic procedures as the main factors that negatively affected training. Extension of the fellowship training program was deemed the optimal option by fellows for addressing the training decrement in the post-pandemic era, while fellowship program directors favored an increase in workload. CONCLUSION: Fellows and their fellowship program directors do not share the same concerns about the impact of COVID-19 pandemic on training programs and they propose different measures to remedy its effects.